Étude du pamphlet luthérien du prêtre-imprimeur Sebastián Martínez. Texte et contexte d’un écrit hérétique (Tolède, septembre 1559) - Ricardo Saez (Les Cahiers de Framespa)
This article is based on an anti-papist pamphlet, dated September 1559, first spread on the streets of Toledo and, later, in those of Ávila and Sevilla. It is based on a work by a printer-priest, Sebastián Martínez, born in Alcalá, forcefully demonstrating tangible traces of a discrete protestant infiltration in the heart of the Spanish Monarchy. Without any doubt its interest lies not much in the repression that the Spanish Inquisition deployed with a ruthlessly efficiency against modern heretical movements but in the discovery that, contrary to Illuminism and Erasmism, Lutheranism is heresy erected into Church. The partial study of the pamphlet highlights the breach between Catholicism and Protestantism, considered a heresy that must be fought and annihilated.